Cancer‐specific survival after diagnosis in men versus women: A pan‐cancer analysis. Issue 3 (30th June 2022) - He, Yan; Su, Yonglin; Zeng, Junsong; Chong, Weelic; Hu, Xiaolin; Zhang, Yu; Peng, Xingchen
Abstract: Comprehensive understanding of cancer‐specific survival differences in gender is critical for cancer prevention and treatment. Based on the Surveillance Epidemiology and End Results database, we included data from the most prevalent cancers (lung, esophageal, liver, pancreatic, stomach, colorectal, kidney, and bladder cancer). Cox proportional hazards regression models were constructed to estimate hazard ratios, simultaneously adjusting for demographic, clinical, and treatment factors. Overall, male patients had a worse cancer‐specific survival than female patients. After adjustment for cancer prevalence with 1:1 matching, gender remained a significant factor in cancer‐specific survival. Among the included cancer types, female patients showed survival benefit in lung, liver, colorectal, pancreatic, stomach, and esophageal cancer, and male patients showed better survival in bladder cancer. Except for kidney cancer, the gender disparity was consistent between cancer patients with nonmetastatic and metastatic disease. Overall, gender appears to be a significant factor influencing cancer‐specific survival, and the prognosis of female patients is better than male patients in most cancers. This work might inspire the development of strategies for gender‐specific precision cancer prevention and treatment. Abstract : Comprehensive understanding of survival differences in gender after cancer diagnosis is critical for cancer prevention and treatment. We compared the gender differences of cancer‐specific survival in lung, esophageal, liver, pancreatic, stomach, colorectal, kidney, and bladder cancer. Totally, gender seemed to be a significant factor influencing cancer‐specific survival, and the prognosis of female patients was better than male patients.